Teaching practice in psychology: interactivity in the classroom - Gomez, Elba (2018)
The present work refers to the analysis that was made, from an interbehavioral approach, of the classes of pre-professional practices of the students of the Psychology Faculty of the National University of San Luis. A qualitative analysis of the observations and class records and practice diaries of 28 practitioners years 2014-2016 was carried out. The non-probabilistic sample and the unit of analysis consisted of written texts of class records during the dictation of the subject psychology of 4 public schools of the city of San Luis and personal diaries of the students. It could be observed that the interactivity in the classes varies according to the educational institution. In turn, most of the student-practitioner interactive behaviors corresponded to the contextual, supplementary and selector level. Finally, the possibilities of interbehavioral analysis of the teacher-student relationship in the class were assessed.